Nitrogen fertiliser value of products from dehydration of pine bark–human urine mixtures under field conditions - Vilakazi, Samukelisiwe P.; Odindo, A. O.; Muchaonyerwa, P. (Frontiers in Soil Science, 2026)
There is limited information on the agronomic performance of fertiliser products from dehydration of mixtures of urine and solid waste materials under field conditions. This study investigated the effects of products derived from dehydration (glasshouse) of pine bark (PB), biochar, and ash mixed with artificial human urine as sources of nitrogen (N) for spinach (Spinacia oleracea) in field conditions. A field trial was conducted at the Ukulinga Research Farm to evaluate the effect of these pine bark urine-based products on spinach growth over two seasons. The products were applied at the recommended N rate for spinach in the first season. The pine bark feedstock, biochar, and ash that were not pretreated with urine were included as reference materials, whereas plots without N and with urea were included as negative and positive controls, respectively. In the second season, the same plots were used without any additional treatment to assess residual effects. In each season, the field trial lasted for approximately 3 months, from 04/06/2024–04/09/2024 and 12/09/2024–04/12/2024. Spinach dry matter yield, nutrient uptake, and tissue micronutrients were determined, together with soil pH, extractable phosphorus (P), and mineral N. The urine-based products improved dry matter yield and N uptake of spinach as compared with the negative control. However, high sodium (Na) concentrations were detected in plant tissues (first season). Residual applications led to an increase in dry matter yield of biochar-U (238 g plot−1) compared with the positive control (155.7 g plot−1). Residual application of urine-based fertilisers reduced the risk of sodium accumulation, as the initial crop absorbed most of the sodium. These findings suggest that urine-based (biochar-U) fertilisers are a viable and sustainable alternative to mineral N fertilisers. This supports the philosophy of circular economy through resource efficiency, as promising option for smallholder farmers, although Na concentrations need to be monitored.